2007
DOI: 10.1016/j.amjopharm.2007.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Correlates of Serum 25-Hydroxyvitamin D Levels in a Sample of Patients with Hip Fracture

Abstract: Sponsor's Role: Indicate sponsor's role in the design, methods, subject recruitment, data collections, analysis and preparation of paper.The study from which the data reported here were derived were part of a larger industry sponsored (Novartis) clinical trial testing the efficacy of a bisphosonate on hip-fracture. The design, analysis, interpretation and preparation of the results reported here were the responsibility and were determined by the lead author. NIH Public AccessAuthor Manuscript

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…17,18 Inadequate vitamin D levels have been demonstrated in patients with osteoporosis, 19 including in hip fracture patients in many countries, although low levels may be influenced by the fracture itself. [20][21][22] It is also important to note that vitamin D deficiency increases with ageing and that this contributes independently to secondary hyperparathyroidism. 23 In addition, serum androgen levels in men are associated with serum 25(OH)D levels and both hormones have a concordant annual periodicity being lowest in late winter, 24 suggesting important, and as yet unidentified, links between the vitamin D and sex-steroid axes.…”
Section: Effects Of Season On Bone Healthmentioning
confidence: 99%
“…17,18 Inadequate vitamin D levels have been demonstrated in patients with osteoporosis, 19 including in hip fracture patients in many countries, although low levels may be influenced by the fracture itself. [20][21][22] It is also important to note that vitamin D deficiency increases with ageing and that this contributes independently to secondary hyperparathyroidism. 23 In addition, serum androgen levels in men are associated with serum 25(OH)D levels and both hormones have a concordant annual periodicity being lowest in late winter, 24 suggesting important, and as yet unidentified, links between the vitamin D and sex-steroid axes.…”
Section: Effects Of Season On Bone Healthmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] There is conflicting evidence with regard to the association of vitamin D deficiency with the occurrence of osteoporotic fractures. [15][16][17][18][19][20] A study from Hong Kong showed that hypovitaminosis D was common among elderly patients with femoral neck fractures. 21 A similar study on Japanese postmenopausal women living in Hawaii did not find any significant association between 25(OH)D and either vertebral or nonvertebral fractures.…”
Section: Figure 1 Scatter Plot Of Ipth Versus 25(oh)d Among All Patimentioning
confidence: 99%
“…Randomized placebo-controlled trials have demonstrated that vitamin D supplementation prevents falls (1) and fractures (2, 3), at least in the 35%-60% of the population with insufficient serum 25-hydroxyvitamin D [25(OH)D] levels (4,5). In addition, epidemiologic evidence links low vitamin D levels with a variety of illnesses, including diabetes, cardiovascular disease, COPD, respiratory infections, autoimmune diseases, and cancers (6), although it remains to be proven that supplements prevent adverse outcomes in these diseases.…”
Section: Current Therapymentioning
confidence: 99%